1991
DOI: 10.1016/0092-8674(91)90244-s
|View full text |Cite
|
Sign up to set email alerts
|

Scrambled exons

Abstract: Using a sensitive assay for RNA expression, we identified several abnormally spliced transcripts in which exons from a candidate tumor suppressor gene (DCC) were scrambled during the splicing process in vivo. Cloning and sequencing of PCR-amplified segments of the abnormally spliced transcripts showed that exons were joined accurately at consensus splice sites, but in an order different from that present in the primary transcript. Four scrambled transcripts were identified, each involving a different pair of e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
588
0
7

Year Published

1992
1992
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 836 publications
(615 citation statements)
references
References 36 publications
8
588
0
7
Order By: Relevance
“…The RNase-resistant products were analysed by gel electrophoresis. Protected (Nigro et al, 1991) and the authors also demonstrated that these products are not polyadenylated. Both results clearly establish that scrambling of exons may occur during the splicing process in vivo.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The RNase-resistant products were analysed by gel electrophoresis. Protected (Nigro et al, 1991) and the authors also demonstrated that these products are not polyadenylated. Both results clearly establish that scrambling of exons may occur during the splicing process in vivo.…”
Section: Resultsmentioning
confidence: 99%
“…Aberrant annealing of homologous sequences or fortuitous protein interactions within introns leading to a particular secondary structure of the pre-mRNA, might facilitate illegitimate interactions of snRNPs to incorrectly paired exons. A possible mechanism for intramolecular splicing generating abnormally spliced product has been proposed (Nigro et al, 1991) which would generate circular RNAs, but an intermolecular reaction is also possible. Trans-splicing mechanisms described in lower eukaryotes (Agabian, 1990) bear no comparison to the scrambled splicing observed here.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Additional studies reported further new examples of circRNAs over the years, [2][3][4][5][6][7][8][9] yet the extent of the prevalence of the circularization phenomenon was not clear, as the available examples remained limited. The advent of high-throughput sequencing revealed that circRNAs are a large class of abundant RNAs with complex developmental-and cellspecific expression patterns.…”
Section: Introductionmentioning
confidence: 99%
“…v Although isolated examples of circularized RNA molecules were already described more than 20 years ago [1,2], it was not until quite recently that the prevalence of circular RNAs (circRNAs) was revealed. The advent of massively parallel sequencing technology allowed researchers to catalogue circRNAs across eukaryotic and prokaryotic systems (e.g., [3][4][5][6][7]).…”
mentioning
confidence: 99%